The correlation between skin type and acne scar severity in young adults - Yessica Mishellin Awaloei; Nawanto Agung Prastowo; Regina Regina (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: Acne is the most common skin disorder, especially in adolescents and youths. Inflammation due to acne may leave scar tissue. The scar severity may correlate with gender and skin type. Objective: This study aims to investigate the correlation between gender, skin type, and acne scar severity in youth. Methods: This is a cross-sectional study with 132 (81 female) medical college students aged from 18 to 23 participated in the study. Skin type was assessed using a Baumann Skin Type questionnaire. Acne scar severity was evaluated using the Qualitative Global Scarring Grading. Skin examination was conducted through the image from the face photograph. Lambda test was used to confirm the correlation between gender, skin type, and acne scar severity. Multiple logistic regression was applied to determine the odd risk of gender and skin type to moderate-severe acne scar. Significance was set at p<0.05.Results: Most of the participants (80.3%) had oily skin, and 22 participants (16.7%) had moderate-severe acne scar. A weak positive correlation was confirmed between skin type and acne scar severity (p<0.01, r=0.3). Oily skin type has 4.3 times greater risk of developing more severe acne scar (p<0.01, 95%CI = 1.90-9.90).Conclusion: Skin type is correlated with acne scar severity. Oily skin type is at greater risk of developing severe acne scar.